2011
DOI: 10.1177/0193945911402848
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Quality of Life in Menopausal Women

Abstract: Use of a wide variety of quality of life (QoL) instruments, each measuring a different aspect of menopause with a different type of underlying scale, has been a major problem in menopause research. The aim of this review was to identify instruments developed for menopausal women and evaluate the psychometric properties and appropriateness of instruments for the study of QoL in menopausal women. Seven measures from 16 papers were chosen for the review. The psychometric evaluations were conducted based on qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
(110 reference statements)
0
20
0
1
Order By: Relevance
“…8 The MENQOL was introduced in 1996 as a tool to assess health-related quality-of-life in the menopausal period, 9 and it is widely used now and has established reliability and validity among women experiencing menopause in many countries. 10 The systematic review of the measurement of QOL for menopausal women in 2012, 11 however, concluded that the MENQOL needed further testing and evaluation of various aspects of its psychometric properties. Future research assessing its psychometric properties with cross-cultural samples may be beneficial in adapting measures to specific contexts and study populations.…”
mentioning
confidence: 99%
“…8 The MENQOL was introduced in 1996 as a tool to assess health-related quality-of-life in the menopausal period, 9 and it is widely used now and has established reliability and validity among women experiencing menopause in many countries. 10 The systematic review of the measurement of QOL for menopausal women in 2012, 11 however, concluded that the MENQOL needed further testing and evaluation of various aspects of its psychometric properties. Future research assessing its psychometric properties with cross-cultural samples may be beneficial in adapting measures to specific contexts and study populations.…”
mentioning
confidence: 99%
“…There is now a growing move to consider negative, hedonic and eudaimonic well-being in tandem, given that they have distinct neural correlates and contribute unique information about health [4,7]. The measurement of well-being provides useful information over and above quality of life (QoL), which is a related construct that has been widely researched in the menopause literature (for reviews see [8,9]). A number of menopause specific QoL measures have been developed (e.g.…”
Section: Introduction Q2mentioning
confidence: 99%
“…In recent decades, a number of instruments have been developed and used to measure quality of life (QoL) in women in menopausal transition. Most of them were designed and used with European or North American Caucasian women, and most have not been tested for psychometric properties in Asian women (Mishra & Kuh, 2010; Schneider, MacLennan, & Feeny, 2008; Shin & Shin, in press). Menopausal experiences may differ among ethnic groups and it may not be appropriate to use the same QoL measure across ethnicities unless linguistic and cultural appropriateness is assessed (Alder, 2002; Schneider et al, 2008).…”
mentioning
confidence: 99%
“…While several menopause‐specific QoL measures have been developed and used in Europe and North America (Mishra & Kuh, 2010; Schneider et al, 2008; Shin & Shin, in press), neither researchers nor clinicians have an ideal menopause‐specific QoL instrument available to them that is efficient, clinically useful, psychometrically sound, and applicable to Korean women. Although some scales have been used to measure QoL among Korean menopausal women (K. B. Kim & Sok, 2010; M. S. Lee et al, 2010; Lim, Cho, & Lee, 2006), most of them are generic measures developed for the general population, not for women in menopausal transition (K. B. Kim & Sok, 2010; Y. H. Kim, Ha, & Shin, 2003; Lim et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation